RESOURCES, TOURISM POTENTIAL IN OC EO - BA THE RELIC AREA - Em, Đỗ Thị Bích Tuyền (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Cultural tourism is a prominent "product" in the source of tourism activities. Oc Eo - Ba The cultural heritage is an important cultural tourism resource. The archaeological cultural heritage of Oc Eo has a special relationship with the history - culture of the Southern region, especially at the beginning of its discovery. Therefore, the archaeological sites in Oc Eo - Ba The relic site (Thao Son, An Giang) are one of the unique resources for An Giang province to exploit and develop a type of cultural tourism based on The tourism potential stands out with the unique archaeological relics and the unique artistic architecture of this ancient culture